Intratumoral Estrogen Receptor Heterogeneity of Expression in Human Epidermal Growth Factor Receptor 2–Positive Breast Cancer as Evaluated by a Brightfield Multiplex Assay. (August 2019) - Masuda, Shinobu; Nitta, Hiroaki; Kelly, Brian D.; Zhang, Wenjun; Farrell, Michael; Dennis, Eslie
Breast cancer (BC) is a heterogeneous disease with evolving genetic alterations and expressions of receptor proteins. Intratumoral heterogeneity (ITH) is considered to be a resistance factor in response to targeted therapies. The current single-slide, single-marker immunohistochemistry techniques cannot accurately assess ITH at the individual cancer cell level. In this study, we develop a novel brightfield multiplex assay to simultaneously assess estrogen receptor (ER) and human epidermal growth factor receptor 2 (HER2) protein markers, together with the HER2 gene and the centromere of chromosome 17 ( CEP17 ) copy numbers, using a single tissue section. The data presented herein demonstrate heterogeneous cancer cell subpopulations in 11 HER2-positive/ER-positive (HER2+/ER+) tumors among 33 BCs analyzed immunohistochemically (HER2 score of 2+ or 3+). The predominant cancer cell subpopulation was HER2+/ER− (50.18%), followed by HER2+/ER+ (39.05%), HER2−/ER+ (4.26%), ER− with HER2 microheterogeneity cancer cells (3.58%), and ER+ with HER2 microheterogeneity cancer cells (2.93%). The three other tumor subtypes, namely, HER2−/ER+, HER2+/ER−, and HER2−/ER−, were more homogeneous, representing 82.59%, 99.22%, and 100% of cancer cells, respectively. This novel assay revealed that HER2+ cancer cells were more predominant than ER+ cancer cells in HER2+/ER+ tumors and provided new insights toward our understanding of BC carcinogenesis.